Data about species of Algae in Stepanivska kosa salt marshes are given with number of their findings in different geographical zones of Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Data about species of Algae in Stepanivska kosa salt marshes are given with number of their findings in different geographical zones of Ukraine.
Keywords: algae, Stepanivska spit, alkaline soil (salt-marshes), not salted soils, phytocoenoses, geographical zones of Ukraine.